The Liquefaction of Sunflower Seed Hulls - KARACA ALBAYRAK, FATMA (TAYLOR & FRANCIS INC, 2014)
Liquefaction of a biomass waste material, namely, sunflower seed hulls, was studied in a laboratory scale stainless-steel reactor. The key parameters investigated were temperature, cold hydrogen pressure, and tetralin to solvent mixture ratio within the ranges of 325-375 degrees C, 10-30 atm., and 0/1-1/1, respectively. A Box-Behnken experimental design was used fixing the liquefaction period at 45 minutes. The effects of parameters on dependent variables, namely, oil + gas, asphaltene, and preasphaltene yields and total conversion were evaluated, and the model equations for dependent variables were developed. It was shown that temperature and tetralin to solvent mixture ratio were the variables of highest significance on liquefaction yields. An optimization study was also done by using the desirability function approach.
Keywords: biomass waste material; Box-Behnken experimental design; desirability function; liquefaction; sunflower seed hulls; PYROLYSIS; ALGORITHM; KINETICS